Coping strategies and stress in mothers of children with autism spectrum condition and ADHD during the COVID 19 pandemic - Cvitkovic, Daniela; Stošić, Jasmina; Wagner Jakab, Ana (Specijalna edukacija i rehabilitacija, 2024)
Introduction. The COVID 19 pandemic and the earthquake, have brought many difficulties for everyone. Families of children with disabilities, face even more difficulties. Objective. The aim of this study is to investigate the coping strategies of mothers of children with autism spectrum disorder or attention deficit hyperactivity disorder and to determine how they are related to mothers’ stress during the first lockdown in Croatia during the COVID-19 pandemic. At the same time, the capital was shaken by an earthquake, so we further investigated the effects of the earthquake on maternal stress. Method. Coping strategies were measured using the Croatian version of the Family Crisis Oriented Personal Evaluation Scales. Stress was measured using the Croatian version of the Perceived Stress Scale. The study was conducted online. The mothers of primary school children (90 of children with autism spectrum disorder and 67 of children with attention deficit hyperactivity disorder) completed the questionnaires. Results. The results of the repeated measures analysis of variance showed that both the mothers of children with autism spectrum disorder and those of children with attention deficit hyperactivity disorder used the reframing strategy most frequently and the mobilizing family to acquire and accept help least frequently. The results of the linear regression analysis showed that reframing and acquiring social support were statistically significant predictors of maternal stress. There were no differences in maternal stress from the earthquake-affected areas compared to other parts of Croatia. Conclusion. The results indicate a need for psychological support for parents of children with disabilities, especially in crisis situations.